The erosion of ultrafine WC-Co - Pugsley, Victoria Antonietta (Centre for Materials Engineering, 2016)
A series of four ultrafine WC-Co alloys of varying cobalt contents has been sintered from powder produced through the spray conversion process. The materials have been characterised and subjected to slurry erosion and cavitation erosion. A further twelve WC-Co alloys of varying grain sizes and cobalt contents have been produced through conventional processes and subjected to the same tests in order to provide data for comparison. The erosion resistance of all the grades tested was found to increase with decreasing grain size, both under cavitation erosion and slurry erosion conditions. Furthermore, a transition from a localised material removal mechanism to a bulk material removal mechanism was observed in both erosive systems as the WC grain size of the material decreased below about lμm. The erosion resistance of sub-micron materials was found to be considerably more sensitive to bulk deformation parameters than that of coarser materials. As a result, ultrafine grades subjected to slurry erosion or cavitation erosion were found to exhibit lifetimes up to seven times greater than those of the best-performing materials with grain sizes above 1 μm. This increase in erosion resistance was achieved without any significant drop in fracture toupness. Significant differences were observed between the response of WC-Co to the two erosive systems, particularly in those materials exhibiting a localised erosion response. Under slurry erosion conditions, these materials displayed increasing erosion resistance with decreasing cobalt content, and both the cobalt and WC phases responded to erosive attack. Under cavitation erosion conditions, however, the opposite trend was observed, and only the cobalt phase responded to erosive attack. Materials exhibiting a bulk erosion response responded in a similar fashion to both forms of erosive attack, although cavitation erosion produced damage to a greater depth. The effect of defects on material performance was found to depend critically on the erosive system.